Mapeamento associativo para produtividade em arroz sob déficit hídrico - Pantalião, Gabriel Feresin (2013)
Drought is an environmental factor which narrows crop production, such as upland rice (Oryza sativa L.). The knowledge of aspects related to drought stress, and plant response to it, may furnish plant breeding programs essential data for the development of tolerant cultivars, and hence with higher yields under such conditions. Association mapping has been a successful approach to elucidate the genetic basis of economically important traits in plants, and afterward in the implementation of marker assisted selection (MAS). Next-generation sequencing (NGS) technologies have been applied in a variety of contexts, including SNP identification and development. Among methodologies for marker discovery and high-throughput genotyping, GBS (Genotyping by Sequencing) points out by its low cost and speed at which samples can be analyzed. The aim of this work was to identify, by GBS, the polymorphism from SNP markers within 283 upland accessions from Embrapa Rice Core Collection (ERiCC) and associate them to yield under drought stress. After filtering the raw data of predetermined stringent parameters, 285.379 SNP were identified in the 12 rice chromosomes. For the association mapping, molecular and phenotypic data were combined for the identification of SNP associated to drought, aiming the subsequent development of a marker set for MAS besides the identification of genes for genetic engineering. The analysis identified 48 SNP associated with the evaluated traits, 13 associated to drought susceptibility index (DSI) and 35 to yield under drought stress. Among the 48 SNP, 35 was anchored in 31 rice genes. Seven genes, out of the 31, possessed SNP associated to DSI, and the other 24 genes to yield under drought stress. These genes may be evaluated to be effectively employed for MAS. If the overexpression of such genes provides an enhanced drought tolerance, they may be used in the development of tolerant rice cultivars.